Preparation method of low-dispersant conductive paste compounded by single-wall tube, Ketjen carbon black and graphene

By using single-wall carbon nanotubes and Kochen carbon black and graphene composite in conductive paste, the problem of insufficient dispersion of conductive fillers is solved, and the conductivity and stability are improved, which is suitable for high-demand Electronics and new energy fields.

CN119480215AInactive Publication Date: 2025-02-18ANHUI BONDRUI NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411622656.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There are dispersion problems in the existing conductive paste during the preparation process, which leads to agglomeration and affects the conductivity.

Method used

The preparation method of low-dispersant conductive paste composited with single-wall carbon nanotubes and Kochen carbon black and graphene is used to form graphene oxide by modifying single-wall carbon nanotubes and Kochen carbon black and using ozone-treated graphene oxide. Crosslinked structure and π-π conjugated network improve dispersion and conductivity.

Benefits of technology

It significantly improves the conductivity and stability of the conductive paste, reduces the use of dispersant, promotes the formation of a conductive network, and is suitable for applications in high-demand electronics and new energy fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480215A_ABST
    Figure CN119480215A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of conductive paste, in particular to a preparation method of low-dispersant conductive paste compounded by a single-wall tube, Ketjen carbon black and graphene. The preparation method of the low-dispersant conductive paste compounded by the single-wall tube, the Ketjen carbon black and the graphene comprises the following steps: step (1) putting a single-wall carbon nanotube, the Ketjen carbon black, the graphene and a binder into a mixer, uniformly mixing, and crushing by a jet mill to obtain uniformly mixed powder; (2) enabling the uniformly mixed powder to pass through an inert atmosphere high-temperature furnace so that the adhesive is carbonized to obtain cross-linked powder; and (3) mixing the cross-linked powder with an organic solvent, heating, carrying out high-speed shearing dispersion to obtain a prepared dispersion liquid, and sequentially carrying out low-pressure homogenization, sanding dispersion, electric removal magnetic separation machine and high-speed emulsification on the dispersion liquid to obtain the low-dispersant conductive paste compounded by the single-wall tube, the ketjen carbon black and the graphene. The conductive paste prepared by the invention still has relatively high stability under the conditions of low dispersant addition amount, low magnetic substance content, high carbon content and low viscosity, the viscosity is low and stable, uniform coating of the conductive paste is facilitated, a more effective conductive network is constructed by high carbon content and good dispersity, the overall performance of the conductive paste is improved, and the conductive paste is suitable for large-scale popularization and application. And the method is more suitable for being applied to the fields of electronics and new energy with high requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive slurries, and in particular relates to a method for preparing a low-dispersant conductive slurry composite of a single-wall tube, Ketjen black and graphene. Background Art

[0002] Conductive paste is a paste-like material made by mixing conductive materials (such as conductive carbon black, metal powder, conductive polymer, etc.) with binders and solvents. This paste has good fluidity, is easy to coat and form, and can maintain its conductive properties after curing.

[0003] Conductive fillers, the main components of existing conductive pastes, include conductive carbon black: such as Ketjen black (CB) and other types of carbon black, which are widely used due to their high specific surface area and excellent conductivity. Metal powder: such as metal powders such as silver and copper, provide higher conductivity, but the cost is relatively high. Conductive polymers: such as polypyrrole (PPy) and polyaniline (PANI), have the advantages of flexibility and lightweight. Binder: used to increase the adhesion and mechanical strength of the slurry. Common binders include polyurethane, polyester and acrylic acid. Solvent: used to adjust the viscosity and fluidity of the slurry. Common solvents include water, organic solvents (such as ethanol, acetone), etc. Commonly used in battery systems such as lithium-ion batteries and supercapacitors as conductive additives and electrode materials. Or used in the field of printed electronics to manufacture printed circuits, sensors and flexible electronic devices.

[0004] In the prior art, conductive fillers have dispersion problems during the preparation of conductive pastes, resulting in agglomeration and affecting the conductivity of the conductive pastes. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a low-dispersant conductive slurry composite of a single-walled tube, Ketjen black and graphene, so as to solve the technical problems in the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for preparing a low-dispersant conductive slurry composited with a single-walled tube, Ketjen black and graphene, comprising the following steps:

[0008] Step (1) putting single-walled carbon nanotubes, ketjen black, graphene and a binder into a mixer and mixing them evenly, and then crushing them by a jet mill to obtain a uniformly mixed powder;

[0009] The uniformly mixed powders in step (2) are passed through a high temperature furnace in an inert atmosphere to carbonize the adhesive to obtain a cross-linked powder;

[0010] Step (3) The cross-linked powder is mixed with an organic solvent and heated for high-speed shear dispersion to obtain a prepared dispersion, and the dispersion is then sequentially subjected to: low-pressure homogenization, sand mill dispersion, electrostatic separator, and high-speed emulsification to obtain a low-dispersant conductive slurry of a single-walled tube, Ketjen black, and graphene composite.

[0011] Preferably, in step (1), the single-walled carbon nanotubes and Ketjen black are modified single-walled carbon nanotubes and modified Ketjen black.

[0012] Preferably, the method for preparing the modified single-walled carbon nanotubes and modified Ketjen black comprises the following steps:

[0013] S1: Add 2.3-4.6 kg of styrene-maleic anhydride copolymer to 10-18 L of N, N-dimethylacetamide, then drop 0.13-0.26 kg of polyethylene glycol diamine into the above solution under stirring, react at 25° C. for 1-3 h, then add 50-100 L of deionized water, filter, and obtain a grafted styrene-maleic anhydride copolymer;

[0014] The structural formula of the grafted styrene-maleic anhydride copolymer is as follows:

[0015]

[0016] S2: Add 1-2 kg of grafted styrene-maleic anhydride copolymer to 6-12 L of N, N-dimethylacetamide, and then add 4-8 kg of single-walled carbon nanotubes or Ketjen black, ultrasonically treat for 30-60 minutes, and then stir at 25° C. for 10-14 hours to obtain modified single-walled carbon nanotubes or modified Ketjen black.

[0017] Preferably, in step (1), the graphene is functionalized graphene oxide.

[0018] Preferably, the method for preparing the functionalized graphene oxide comprises the following steps:

[0019] P1: 0.63-1.26 kg, 0.4 wt% graphene oxide aqueous solution was treated with bubbling ozone gas generated by an ozone generator at 65-75 ° C for 110-130 min, 38-76 g oxalic acid was added and stirred for 3-5 h, filtered, and dried at 55-65 ° C for 20-28 h to obtain cross-linked graphene oxide;

[0020] P2: Add 10-18 g of 4-aminopyridine to 60-120 mL of N-methyl-2-pyrrolidone, then add 1.2-2.4 g of cross-linked graphene oxide, stir and disperse at 75-85° C. for 20-28 h, and finally vacuum dry at 60-70° C. for 12-24 h to obtain functionalized graphene oxide.

[0021] Preferably, in step (1), the mass ratio of single-walled carbon nanotubes, Ketjen black, graphene and binder is (0.5-25)(1.0-49):(1.0-49):(0.1-3.0); the binder includes at least one of polyvinyl chloride, polyvinylidene fluoride, polyvinyl alcohol, polyethylene glycol and polyvinyl pyrrolidone.

[0022] Preferably, in step (1), the mixing temperature of the mixer is 25-40°C, the stirring speed is 2000-8000rpm, and the stirring time is 5-30min; and the particle size D50 of the crushed powder is 2.5-10.0um.

[0023] Preferably, in step (2), the inert gas in the inert atmosphere high temperature furnace includes one of nitrogen, argon, hydrogen-argon, and hydrogen-nitrogen mixed gas; the carbonization temperature is 600-1000° C., and the carbonization time is 3-12 hours.

[0024] Preferably, in the step (3), the mass ratio of the cross-linked powder to the organic solvent is (2.0-30):(70.0-98.0); the organic solvent comprises at least one of ethanol, isopropanol, N-methylpyrrolidone, and N-vinylpyrrolidone; and the high-speed shear dispersion conditions are: the high-speed shear dispersion temperature is 60-80° C., the high-speed shear dispersion speed is 1000-2000 rpm, and the high-speed shear dispersion time is 1-2 h.

[0025] Preferably, in the step (3), the low-pressure homogenization conditions are: the low-pressure homogenization pressure is 60-80Mpa, the low-pressure homogenization temperature is lower than 50°C, and the low-pressure homogenization time is 1.0-1.5h; the sand milling conditions are: the sand milling speed is 2200-2600rpm, the material temperature is 30-50°C, and the sand milling time is 0.5-1.0h; the electromagnetism separator conditions are: the rated magnetic field of the electromagnetism separator is 23000-28000GS, the number of demagnetization passes is 1-3 times, and the material temperature is lower than 45°C; the high-speed emulsification conditions are: the high-speed emulsification speed is 1800-2200rpm, the high-speed emulsification time is 1.0-2.0h, and the material temperature is lower than 30°C.

[0026] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0027] 1. The present invention utilizes polyethylene glycol diamine grafted styrene maleic anhydride copolymer to modify single-walled carbon nanotubes or Ketjen black through π-π conjugation and positive charge interaction. The enhanced steric hindrance and electrostatic repulsion provided by the organic amine chain make the single-walled carbon nanotubes or Ketjen black exhibit excellent dispersibility in organic solvents, avoid defects such as powder agglomeration, and improve the conductivity of the conductive paste.

[0028] 2. In the present invention, the graphene oxide treated with ozone provides more uniform oxygen-containing groups on the surface of the graphene oxide, provides a continuous transfer pathway for protons in the interlayer nanochannels, and improves the conductivity of the graphene oxide. Then, it is modified with oxalic acid to reduce the swelling ratio and improve the proton conductivity. The cross-linked graphene oxide is relatively active and can react with a variety of functional materials containing active groups. 4-aminopyridine is grafted onto the cross-linked graphene oxide, and amino groups and pyridine rings can be introduced. The grafted 4-aminopyridine can interact with the π-electron cloud of the graphene oxide to enhance the mobility of electrons and improve the electronic conductivity of the graphene oxide. At the same time, the amino groups undergo amidation and ring-opening reactions with the carboxyl and epoxy groups on the surface of the graphene oxide, which also provide active sites for cross-linking. The enhanced cross-linked network forms a continuous conductive path to improve the overall conductivity and the conductivity of the conductive paste.

[0029] 3. The present invention uses a carbonized adhesive to form a uniform cross-linked structure between Ketjen black, single-walled tubes and graphene, thereby preventing the agglomeration of single-walled tubes, which not only reduces the amount of dispersant used, but also promotes the formation of a conductive network, improves the conductivity and stability of the slurry, and the Ketjen black and single-walled tubes play a bridging and filling role respectively; the obtained low-dispersant conductive slurry still has high stability under the conditions of low dispersant addition, low magnetic material, high carbon content and low viscosity, and low viscosity and stability are conducive to the uniform coating of the conductive slurry, and high carbon content and good dispersibility construct a more effective conductive network, improve the overall performance of the conductive slurry, and make it more suitable for application in high-demand electronics and new energy fields; the three-dimensional conductive network of points, lines and surfaces, the rich spatial mesh structure and high stability can achieve better electron and ion transmission effects, better play the performance of single-walled tubes, and cooperate with modified single-walled carbon nanotubes or modified Ketjen black and functionalized graphene oxide to improve the conductivity of the conductive slurry. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 It is a process flow chart of preparing the low-dispersant conductive slurry composited with single-walled tube, Ketjen black and graphene of the present invention;

[0032] Figure 2 is a scanning electron microscope (SEM) micrograph of the conductive paste of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] This embodiment discloses a method for preparing modified single-walled carbon nanotubes, comprising the following steps:

[0036] S1: 3.5 kg of styrene-maleic anhydride copolymer was added to 14 L of N, N-dimethylacetamide, and then 0.2 kg of polyethylene glycol diamine was dropped into the above solution under stirring, reacted at 25 ° C for 2 h, and then added to 75 L of deionized water, filtered, to obtain a grafted styrene-maleic anhydride copolymer;

[0037] S2: 1.5 kg of grafted styrene-maleic anhydride copolymer was added to 10 L of N, N-dimethylacetamide, and then 6 kg of single-walled carbon nanotubes were added. After ultrasonic treatment for 45 minutes, the mixture was stirred at 25° C. for 12 hours to obtain modified single-walled carbon nanotubes.

[0038] Example 2

[0039] This embodiment discloses a method for preparing modified Ketjen black, comprising the following steps:

[0040] S1: 4 kg of styrene-maleic anhydride copolymer was added to 14 L of N, N-dimethylacetamide, and then 0.18 kg of polyethylene glycol diamine was dropped into the above solution under stirring, reacted at 25 ° C for 2 h, and then added to 75 L of deionized water, filtered, to obtain a grafted styrene-maleic anhydride copolymer;

[0041] S2: 1.5 kg of grafted styrene-maleic anhydride copolymer was added to 9 L of N, N-dimethylacetamide, and then 6.5 kg of Ketjen black was added. After ultrasonic treatment for 45 minutes, the mixture was stirred at 25° C. for 12 hours to obtain modified Ketjen black.

[0042] Example 3

[0043] This embodiment discloses a method for preparing functionalized graphene oxide, comprising the following steps:

[0044] P1: 0.95 kg, 0.4 wt% graphene oxide aqueous solution was treated with bubbling ozone gas generated by an ozone generator at 70° C. for 120 min, 57 g oxalic acid was added and stirred for 4 h, filtered, and dried at 60° C. for 24 h to obtain cross-linked graphene oxide;

[0045] P2: 14 g of 4-aminopyridine was added to 90 mL of N-methyl-2-pyrrolidone, and then 1.8 g of cross-linked graphene oxide was added, stirred and dispersed at 80 °C for 24 h, and finally vacuum dried at 65 °C for 18 h to obtain functionalized graphene oxide.

[0046] Example 4

[0047] See also Figure 1 As shown, this embodiment discloses a method for preparing a low-dispersant conductive slurry composite of a single-walled tube, Ketjen black, and graphene, comprising the following steps:

[0048] Step (1) 15 g of single-walled carbon nanotubes, 25 g of Ketjen black, 25 g of graphene, and 1.5 g of polyvinyl chloride are put into a mixer and mixed evenly, and then crushed by a jet mill to obtain a uniformly mixed powder; the mixing temperature of the mixer is 30° C., the stirring speed is 5000 rpm, and the stirring time is 15 min;

[0049] Step (2) the uniformly mixed powder is placed in a high temperature furnace in a nitrogen inert atmosphere at 800° C. to carbonize the adhesive for 7 hours to obtain a cross-linked powder;

[0050] Step (3) 15 g of the cross-linked powder was mixed with 85 g of ethanol, and high-speed shearing and dispersion was performed at 70° C. and a rotation speed of 1500 rpm for 1.5 h to obtain a prepared dispersion liquid, and the dispersion liquid was then sequentially subjected to: low-pressure homogenization, sand mill dispersion, electrostatic separator, and high-speed emulsification to obtain a low-dispersant conductive slurry of single-walled tubes, Ketjen black, and graphene composites;

[0051] Low-pressure homogenization conditions: low-pressure homogenization pressure is 70Mpa, low-pressure homogenization temperature is lower than 50°C, and low-pressure homogenization time is 1.2h; sanding conditions: sanding speed is 2400rpm, material temperature is 40°C, and sanding time is 0.8h. Electrostatic separator conditions: rated magnetic field of electrostatic separator is 25000GS, demagnetization times are 2 times, and material temperature is lower than 45°C; high-speed emulsification conditions: high-speed emulsification speed is 2000rpm, high-speed emulsification time is 1.5h, and material temperature is lower than 30°C.

[0052] Example 5

[0053] See also Figure 1 As shown, this embodiment discloses a method for preparing a low-dispersant conductive slurry composite of a single-walled tube, Ketjen black, and graphene, comprising the following steps:

[0054] Step (1) 0.5 g of single-walled carbon nanotubes, 4 g of Ketjen black, 2 g of graphene, and 0.2 g of polyvinylidene fluoride are put into a mixer and mixed evenly, and then crushed by a jet mill to obtain a uniformly mixed powder; the mixing temperature of the mixer is 25° C., the stirring speed is 8000 rpm, and the stirring time is 5 min;

[0055] Step (2) the uniformly mixed powder is placed in a high temperature furnace with an argon inert atmosphere at 1000° C. to carbonize the adhesive for 3 hours to obtain a cross-linked powder;

[0056] Step (3) 2.0 g of the cross-linked powder is mixed with 98 g of isopropanol, and high-speed shearing and dispersion is performed at 80° C. and 1000 rpm for 2 h to obtain a prepared dispersion, and the dispersion is then sequentially subjected to: low-pressure homogenization, sand mill dispersion, electromagnetism separator, and high-speed emulsification to obtain a low-dispersant conductive slurry of a single-walled tube, Ketjen black, and graphene composite;

[0057] Low-pressure homogenization conditions: low-pressure homogenization pressure is 60Mpa, low-pressure homogenization temperature is lower than 50°C, and low-pressure homogenization time is 1.5h; sanding conditions: sanding speed is 2200rpm, material temperature is 50°C, and sanding time is 0.5h. Electrostatic separator conditions: rated magnetic field of the electrostatic separator is 28000GS, demagnetization times is 1, and material temperature is lower than 45°C; high-speed emulsification conditions: high-speed emulsification speed is 2200rpm, high-speed emulsification time is 1.0h, and material temperature is lower than 30°C.

[0058] Example 6

[0059] See also Figure 1 As shown, this embodiment discloses a method for preparing a low-dispersant conductive slurry composite of a single-walled tube, Ketjen black, and graphene, comprising the following steps:

[0060] Step (1) 25 g of single-walled carbon nanotubes, 49 g of Ketjen black, 30 g of graphene, and 3.0 g of polyvinyl alcohol are put into a mixer and mixed evenly, and then crushed by a jet mill to obtain a uniformly mixed powder; the mixing temperature of the mixer is 40° C., the stirring speed is 2000 rpm, and the stirring time is 30 min;

[0061] Step (2) the uniformly mixed powder is placed in a high temperature furnace in an inert atmosphere of a hydrogen-argon mixed gas at 600° C. to carbonize the adhesive for 12 hours to obtain a cross-linked powder;

[0062] Step (3) 30 g of the cross-linked powder was mixed with 70 g of N-methylpyrrolidone, and high-speed shearing and dispersion was performed at 60° C. and 2000 rpm for 1 hour to obtain a prepared dispersion liquid, and the dispersion liquid was then sequentially subjected to: low-pressure homogenization, sand mill dispersion, electromagnetism separator, and high-speed emulsification to obtain a low-dispersant conductive slurry of single-walled tubes, Ketjen black, and graphene composites;

[0063] Low-pressure homogenization conditions: low-pressure homogenization pressure is 80Mpa, low-pressure homogenization temperature is lower than 50°C, and low-pressure homogenization time is 1.0h; sand grinding conditions: sand grinding speed is 2600rpm, material temperature is 30°C, and sand grinding time is 1.0h. Electrostatic separator conditions: rated magnetic field of electrostatic separator is 23000GS, demagnetization times are 3 times, and material temperature is lower than 45°C; high-speed emulsification conditions: high-speed emulsification speed is 1800rpm, high-speed emulsification time is 2.0h, and material temperature is lower than 30°C.

[0064] Example 7

[0065] See also Figure 1 As shown, this embodiment discloses a method for preparing a low-dispersant conductive slurry composite of a single-walled tube, Ketjen black, and graphene, comprising the following steps:

[0066] Step (1) 10 g of single-walled carbon nanotubes, 35 g of Ketjen black, 12 g of graphene and 1.5 g of polyethylene glycol are put into a mixer and mixed evenly, and then crushed by a jet mill to obtain a uniformly mixed powder; the mixing temperature of the mixer is 30° C., the stirring speed is 7000 rpm, and the stirring time is 10 min;

[0067] Step (2) the uniformly mixed powder is placed in a high temperature furnace in an inert atmosphere of a hydrogen-nitrogen mixed gas at 700° C. to carbonize the adhesive for 10 hours to obtain a cross-linked powder;

[0068] Step (3) 20 g of the cross-linked powder was mixed with 80 g of N-vinylpyrrolidone, and high-speed shearing and dispersion was performed at 70° C. and a rotation speed of 1200 rpm for 2 h to obtain a prepared dispersion liquid, and the dispersion liquid was then sequentially subjected to: low-pressure homogenization, sand mill dispersion, electromagnetism separator, and high-speed emulsification to obtain a low-dispersant conductive slurry of single-walled tubes, Ketjen black, and graphene composites;

[0069] Low-pressure homogenization conditions: low-pressure homogenization pressure is 65Mpa, low-pressure homogenization temperature is lower than 50°C, and low-pressure homogenization time is 1.2h; sanding conditions: sanding speed is 2300rpm, material temperature is 45°C, and sanding time is 0.6h. Electrostatic separator conditions: rated magnetic field of electrostatic separator is 27000GS, demagnetization times is 1 time, and material temperature is lower than 45°C; high-speed emulsification conditions: high-speed emulsification speed is 2100rpm, high-speed emulsification time is 1.2h, and material temperature is lower than 30°C.

[0070] Example 8

[0071] See also Figure 1 As shown, this embodiment discloses a method for preparing a low-dispersant conductive slurry composite of a single-walled tube, Ketjen black, and graphene, comprising the following steps:

[0072] Step (1) 20 g of single-walled carbon nanotubes, 15 g of Ketjen black, 20 g of graphene, and 2.1 g of polyvinyl pyrrolidone are put into a mixer and mixed evenly, and then crushed by a jet mill to obtain a uniformly mixed powder; the mixing temperature of the mixer is 35° C., the stirring speed is 3000 rpm, and the stirring time is 25 min;

[0073] Step (2) the uniformly mixed powder is placed in a high temperature furnace in a nitrogen inert atmosphere at 900° C. to carbonize the adhesive for 5 hours to obtain a cross-linked powder;

[0074] Step (3) 10 g of the cross-linked powder was mixed with 90 g of N-methylpyrrolidone, and high-speed shearing and dispersion was performed at 65° C. and a rotation speed of 1800 rpm for 1 hour to obtain a prepared dispersion liquid, and the dispersion liquid was then sequentially subjected to: low-pressure homogenization, sand mill dispersion, electromagnetism separator, and high-speed emulsification to obtain a low-dispersant conductive slurry of a single-walled tube, Ketjen black, and graphene composite;

[0075] Low-pressure homogenization conditions: low-pressure homogenization pressure is 75Mpa, low-pressure homogenization temperature is lower than 50°C, and low-pressure homogenization time is 1.2h; sanding conditions: sanding speed is 2400rpm, material temperature is 35°C, and sanding time is 0.8h. Electrostatic separator conditions: rated magnetic field of the electrostatic separator is 24000GS, demagnetization times are 3 times, and material temperature is lower than 45°C; high-speed emulsification conditions: high-speed emulsification speed is 1900rpm, high-speed emulsification time is 1.8h, and material temperature is lower than 30°C.

[0076] Comparative Example 1

[0077] Comparative Example 1 Compared with Example 4, in the process of preparing the low-dispersant conductive slurry of single-walled tube and Ketjen black and graphene composite in Comparative Example 1, no carbonized adhesive is used, and other conditions remain unchanged.

[0078] Comparative Example 2

[0079] Comparative Example 2 Compared with Example 4, in Comparative Example 2, single-walled carbon nanotubes and Ketjen black were not modified during the preparation of the low-dispersant conductive slurry composite of single-walled tubes, Ketjen black and graphene.

[0080] Comparative Example 3

[0081] Comparative Example 3 Compared with Example 4, in Comparative Example 3, graphene oxide is not functionalized during the process of preparing the low-dispersant conductive slurry of single-walled tube and Ketjen black and graphene composite.

[0082] Experimental example

[0083] The properties of the single-walled tube and the low-dispersant conductive slurry composited with Ketjen black and graphene prepared in Examples 4-8 and Comparative Examples 1-3 were tested.

[0084] Determination method

[0085] For the single-walled tube and Ketjen black, graphene composite low-dispersant conductive paste prepared in the above Examples 4-8 and Comparative Examples 1-3, the conductive pastes of the above Examples were tested for pole piece resistivity and viscosity; the viscosity test was to put 0.4 ml of the conductive paste into an EHD viscometer with a 3-degree conical rotor, and measure the viscosity at 0.5 rpm at 25°C. The lower the viscosity, the better its fluidity; the performance measurement results of Examples 4-8 and Comparative Examples 1-3 are shown in Table 1:

[0086] Table 1

[0087] Group Electrode sheet resistivity (Ω·cm) Viscosity (Pa·s) Example 4 4.1 232 Example 5 4.6 230 Example 6 4.4 238 Example 7 4.9 229 Example 8 5.2 243 Comparative Example 1 9.8 358 Comparative Example 2 11.7 339 Comparative Example 3 10.5 342

[0088] It can be seen from Table 1 that the low-dispersant conductive pastes of single-walled tubes, Ketjen black and graphene prepared in Examples 4-8 have good conductivity; from the comparison between Comparative Example 1 and Example 4, it can be seen that in the process of preparing the low-dispersant conductive paste of single-walled tubes, Ketjen black and graphene, the present invention modifies the single-walled carbon nanotubes and Ketjen black, which can significantly improve the conductivity of the conductive paste; from the comparison between Comparative Example 3 and Example 4, it can be seen that in the process of preparing the low-dispersant conductive paste of single-walled tubes, Ketjen black and graphene, the present invention functionalizes the oxide graphene, which can significantly improve the conductivity of the conductive paste.

[0089] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0090] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a low-dispersant conductive slurry composite of a single-walled tube, Ketjen black and graphene, characterized in that: The following steps are involved: Step (1) putting single-walled carbon nanotubes, ketjen black, graphene and a binder into a mixer and mixing them evenly, and then crushing them by a jet mill to obtain a uniformly mixed powder; The uniformly mixed powders in step (2) are passed through a high temperature furnace in an inert atmosphere to carbonize the adhesive to obtain a cross-linked powder; Step (3) The cross-linked powder is mixed with an organic solvent and heated for high-speed shear dispersion to obtain a prepared dispersion, and the dispersion is then sequentially subjected to: low-pressure homogenization, sand mill dispersion, electrostatic separator, and high-speed emulsification to obtain a low-dispersant conductive slurry of a single-walled tube, Ketjen black, and graphene composite.

2. The method for preparing the low-dispersant conductive slurry composited with single-walled tube, Ketjen black and graphene according to claim 1, characterized in that: In the step (1), the single-walled carbon nanotubes and Ketjen black are modified single-walled carbon nanotubes and modified Ketjen black.

3. The method for preparing the low-dispersant conductive slurry composited with single-walled tube, Ketjen black and graphene according to claim 2, characterized in that: The preparation method of the modified single-walled carbon nanotube and modified Ketjen black comprises the following steps: S1: Add 2.3-4.6 kg of styrene-maleic anhydride copolymer to 10-18 L of N, N-dimethylacetamide, then drop 0.13-0.26 kg of polyethylene glycol diamine into the above solution under stirring, react at 25° C. for 1-3 h, then add 50-100 L of deionized water, filter, and obtain a grafted styrene-maleic anhydride copolymer; S2: Add 1-2 kg of grafted styrene-maleic anhydride copolymer to 6-12 L of N, N-dimethylacetamide, and then add 4-8 kg of single-walled carbon nanotubes or Ketjen black, ultrasonically treat for 30-60 minutes, and then stir at 25° C. for 10-14 hours to obtain modified single-walled carbon nanotubes or modified Ketjen black.

4. The method for preparing the low-dispersant conductive slurry composited with single-walled tube, Ketjen black and graphene according to claim 1, characterized in that: In the step (1), the graphene is functionalized graphene oxide.

5. The method for preparing the low-dispersant conductive slurry composited with single-walled tube, Ketjen black and graphene according to claim 4, characterized in that: The method for preparing the functionalized graphene oxide comprises the following steps: P1: 0.63-1.26 kg, 0.4 wt% graphene oxide aqueous solution was treated with bubbling ozone gas generated by an ozone generator at 65-75 ° C for 110-130 min, 38-76 g oxalic acid was added and stirred for 3-5 h, filtered, and dried at 55-65 ° C for 20-28 h to obtain cross-linked graphene oxide; P2: Add 10-18 g of 4-aminopyridine to 60-120 mL of N-methyl-2-pyrrolidone, then add 1.2-2.4 g of cross-linked graphene oxide, stir and disperse at 75-85° C. for 20-28 h, and finally vacuum dry at 60-70° C. for 12-24 h to obtain functionalized graphene oxide.

6. The method for preparing the low-dispersant conductive slurry composited with single-walled tube, Ketjen black and graphene according to claim 1, characterized in that: In the step (1), the mass ratio of single-walled carbon nanotubes, Ketjen black, graphene and binder is (0.5-25)(1.0-49):(1.0-49):(0.1-3.0); the binder includes at least one of polyvinyl chloride, polyvinylidene fluoride, polyvinyl alcohol, polyethylene glycol and polyvinyl pyrrolidone.

7. The method for preparing the low-dispersant conductive slurry composited with single-walled tube, Ketjen black and graphene according to claim 1, characterized in that: In the step (1), the mixing temperature of the mixer is 25-40° C., the stirring speed is 2000-8000 rpm, and the stirring time is 5-30 min; and the particle size D50 of the crushed powder is 2.5-10.0 um.

8. The method for preparing the low-dispersant conductive slurry composited with single-walled tube, Ketjen black and graphene according to claim 1, characterized in that: In the step (2), the inert gas in the inert atmosphere high temperature furnace includes one of nitrogen, argon, hydrogen-argon, and hydrogen-nitrogen mixed gas; the carbonization temperature is 600-1000° C., and the carbonization time is 3-12 hours.

9. The method for preparing the low-dispersant conductive slurry composited with single-walled tube, Ketjen black and graphene according to claim 1, characterized in that: In the step (3), the mass ratio of the cross-linked powder to the organic solvent is (2.0-30):(70.0-98.0); the organic solvent comprises at least one of ethanol, isopropanol, N-methylpyrrolidone, and N-vinylpyrrolidone; and the high-speed shear dispersion conditions are: the high-speed shear dispersion temperature is 60-80° C., the high-speed shear dispersion speed is 1000-2000 rpm, and the high-speed shear dispersion time is 1-2 h.

10. The method for preparing the low-dispersant conductive slurry composited with single-walled tube, Ketjen black and graphene according to claim 1, characterized in that: In the step (3), the low-pressure homogenization conditions are as follows: the low-pressure homogenization pressure is 60-80Mpa, the low-pressure homogenization temperature is lower than 50°C, and the low-pressure homogenization time is 1.0-1.5h; the sand milling conditions are as follows: the sand milling speed is 2200-2600rpm, the material temperature is 30-50°C, and the sand milling time is 0.5-1.0h; the electromagnetism separator conditions are as follows: the rated magnetic field of the electromagnetism separator is 23000-28000GS, the number of demagnetization passes is 1-3 times, and the material temperature is lower than 45°C; the high-speed emulsification conditions are as follows: the high-speed emulsification speed is 1800-2200rpm, the high-speed emulsification time is 1.0-2.0h, and the material temperature is lower than 30°C.